Ventajas de la creacion de poblaciones mejoradas de Psidium Salutare (H.B.K.) Berg (Guayabita del Pinar) - Noda Jimenez, A.L.=700 1 Junco Cruz, L.; Sotolongo Sospedra, R.; Geada Lopez, G.; Medina Malagon, M.; Paez Vazquez, C.
(Es, En)
Ilus., 5 ref.
Keywords: PSIDIUM; CONSERVACION DEL GERMOPLASMA; FITOMEJORAMIENTO; CUBA; PSIDIUM SALUTARE; REVISTA FORESTAL BARACOA